FLUVIAL GEOCHEMISTRY APPLIED TO THE EVALUATION OF CHEMICAL WEATHERING RATES AND SOIL REMOVAL IN RIO CLARO FORMATION - Couto Junior, Antonio Aparecido [UNESP]; Conceicao, Fabiano Tomazini da [UNESP]; Fernandes, Alexandre Martins [UNESP]; Lupinacci, Cenira Maria [UNESP]; Spatti Junior, Eder Paulo [UNESP] (Uniao Geomorfologia Brasileira, 2016)
This study aimed to determine through fluvial geochemistry chemical weathering rates and soil removal of Rio Claro formation in Cachoeirinha stream basin, Rio Claro (SP). In the river mouth the discharge, total dissolved solids (TDS), total suspended solids (TSS), temperature, pH, electrical conductivity and dissolved oxygen were analyzed. The results showed an annual cations and anions flow of 114.3 t a(-1) and weathering rates of 0.7 m Ma(-1) of minerals from Rio Claro formation. These results indicate a low rate of chemical weathering of rocks relative to other rock types (alkaline rocks, carbonates, basalts, granites, schists and gneisses). About the soil removal it was obtained the value of 169.8 t a(-1) with a rate of 9.6 m Ma(-1) and these values are consistent with the results of studies conducted in southeastern Brazil. Thus, in the current climate there is a predominant soil removal in relation to their training or a positive balance of denudation.
Keywords: Balance of Denudation; Sedimentary Rocks; Silicate Minerals